Rare bird documentation form for Peregrine Falcon at Sand Point at Coralville Reservoir, 1977 - Halmi, Nicholas S.et al (1977)
Rare bird documentation form for a Peregrine Falcon at Sand Point at Coralville Reservoir in Johnson County, IA on May 3, 1977. Epson - sheet feed